(untitled) (Eurasian Journal of Philology Science and Education, 2019)
In this article the bilingualism problem is considered. And also concepts about their distributions and features are given. Each bilingual writer has inherent only to him a style of the letter, that is language features. In works by writersbilingual it is possible to see features of language images of the whole world. To collect words which define a language image of the world and to consider their division into lexical sema. Bilinguals writers use several words which belong to national knowledge of the Kazakh people. Also to take psychological components of the language relations in attention and to study dictionary actions. Each nation perceives the world in the native language by means of the different language facts, the language world of the environment, generally, are similar in logical images of the world in human consciousnesses. The similarity between the phenomena gives the chance to replenishment to lexemes. In creation of a world image at people all mental actions work: sensuality, concept, feeling, understanding and thought, selfunderstanding, etc. The image of the Universe is primary condition of a concept of the world.